2017
DOI: 10.1101/131607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity/Type II Diabetes Alters Macrophage Polarization Resulting in a Fibrotic Tendon Healing Response

Abstract: Type II Diabetes (T2DM) dramatically impairs the tendon healing response, resulting in decreased collagen organization and mechanics relative to non-diabetic tendons. Despite this burden, there remains a paucity of information regarding the mechanisms that govern impaired healing of diabetic tendons. Mice were placed on either a high fat diet (T2DM) or low fat diet (lean) and underwent flexor tendon transection and repair surgery. Healing was assessed via mechanical testing, histology and changes in gene expre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Despite the well‐known complications that arise during diabetic tendon healing, there are few animal studies that examine the mechanisms and cell types involved in the abnormal healing response (Table ). Similar to what is seen in clinical cases of T2DM tendon injury, T2DM rodent models exhibit impaired tendon healing . More specifically, using the DIO mouse model, David et al reported increased extracellular matrix disorganization, limited tenocyte migration, and impaired biomechanical properties following a biopsy punch injury to the FDL mid‐substance.…”
Section: Diabetic Tendon Healingmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite the well‐known complications that arise during diabetic tendon healing, there are few animal studies that examine the mechanisms and cell types involved in the abnormal healing response (Table ). Similar to what is seen in clinical cases of T2DM tendon injury, T2DM rodent models exhibit impaired tendon healing . More specifically, using the DIO mouse model, David et al reported increased extracellular matrix disorganization, limited tenocyte migration, and impaired biomechanical properties following a biopsy punch injury to the FDL mid‐substance.…”
Section: Diabetic Tendon Healingmentioning
confidence: 77%
“…As with human cases, the majority of diabetic mouse models are obese with varying levels of severity. Male C57BL/6J mice are commonly used to model diet‐induced obesity (DIO) and associated T2DM as they become obese and develop decreased glucose tolerance with moderate insulin resistance when fed a high‐fat diet (HFD) . The DIO mouse model also recapitulates hallmark complications of human T2DM including impaired wound healing and peripheral neuropathy .…”
Section: Molecular Mechanisms Of Disrupted Homeostasis In T2dm Tendonsmentioning
confidence: 99%
“…Similarly, in obese/T2DM rodents, flexor tendons heal with increased fibrosis and significantly impaired mechanical properties (75,141,142). This poor healing response is associated with increased expression of M1 macrophage markers in addition to increased and sustained expression of M2 macrophage markers throughout healing in obese/T2DM mice compared to controls (75). Though the reason for poor tendon healing in obese and/or diabetic patients is likely multifactorial, these studies further imply that inflammation is a critical driver of tendon fibrosis.…”
Section: Factors That Impact Tendon Healingmentioning
confidence: 84%
“…Fibrotic tendon disorders and complications during tendon healing are common in both obese and/or T2DM patients. Similarly, in obese/T2DM rodents, flexor tendons heal with increased fibrosis and significantly impaired mechanical properties (75,141,142). This poor healing response is associated with increased expression of M1 macrophage markers in addition to increased and sustained expression of M2 macrophage markers throughout healing in obese/T2DM mice compared to controls (75).…”
Section: Factors That Impact Tendon Healingmentioning
confidence: 99%
See 1 more Smart Citation